Health promotion within a sex on premises venue: notes from the field. (December 2015) - Debattista, Joseph
Despite their historical controversy as perceived public health risks, sex on premises venues (SOPV) such as saunas and sex clubs can afford structured opportunities for on-site sexual health interventions within a supportive, regulated and confidential environment. Building upon previous interventions to deliver on-site clinical and health promotion programmes, an education and referral outreach service was established at one particular SOPV within the inner Brisbane city area. This report outlines the experiences of that on-site education/referral outreach over a five-year period. The service did afford opportunities for a minority of patrons to discuss concerns, resolve misunderstandings, obtain advice and referral, and would suggest that a health promotion presence within such a venue is a useful mechanism for engaging with highly sexually active men.